(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article discusses phraseological units in a language, its domain. The concepts of phraseological units are given in different languages using various terms and interpretations, which can be based on many lexical units.